A channel matching scheme for cross-chain. (5th May 2020) - She, Wei; Gu, Zhi-hao; Liu, Wei; Chen, Jian-sen; Wang, Bo; Tian, Zhao
At present, the cross-chain technology works on becoming a bridge to build trust and transmit the information among chains. However, most of the existing schemes have poor universality, and they also have insufficient protection for the process of information cross-chain transmission. Contraposing the deficiencies above, we propose a channel matching scheme for cross-chain (CMSCC), CMSCC combines the ideas of the relay chain scheme and the channel in Fabric. The relay chain named chain-anchor and relay-chain (CARC) can be connected to other blockchains by multi-blockchain communication and consociation protocol (MBCCP). In CARC, the order peers will match the peers which on different chains and will create the peer matching channel (PMC) among matched peers. So, the information can be transmitted among matched peers. Finally, the experiment verifies that CMSCC enables information to be transmitted among chains through PMC, and CMSCC can also protect the process of information cross-chain transmission by PMC simultaneously.